HUBUNGAN AKTIVITAS FISIK DAN KECEMASAN DENGAN KEJADIAN PREMENSTRUAL SYNDROM (PMS) PADA REMAJA PUTRI DI DESA KETAPANG KECAMATAN MAUK KABUPATEN TANGERANG BANTEN - Sri Wiwin (Yayasan Nusantara Hasana Berdikari, 2023)
Premenstrual is one of the menstrual cycle disorders that often appears in women in the form of a group of physical, psychological and emotional symptoms. Objective of this study is to determine the relationship between physical activity and anxiety with the incidence of Premenstrual Syndrom (PMS) in young women in Ketapang village, Mauk District, Tangerang Regency, Banten. This research is a type of quantitative research with a method of collecting data on the relationship between physical activity and anxiety with premenstrual syndrom events in young women in Ketapang village, Mauk District, Tangerang Banten Regency using Google Form, obtained by distributing questionnaires to 120 respondents. Chil square test, obtained a p-value of 0.000 < 0.05 which means that there is a relationship between anxiety and the incidence of premenstrual syndrom in young women in Ketapang Village, Mauk District, Tangerang Regency, Banten. Hormonal changes are one of the factors causing PMS. Adolescents with anxiety have a risk of experiencing AN STD so that the high level of anxiety will be, the more severe the PMS symptoms felt.